Absence of Reliable Screening Methods That Prove the Use of Gene Doping in Sports - AL-Dafrawi, Ahmad Saad Ahmad (2023)
Sport raises the level of human physical activity within the limits of genetic traits. The results of gene therapy have attracted some to think of using its technologies to create an “indomitable athlete.” World Anti-Doping Agency (WADA) applies uncertain genetic testing procedures to establish cases of this type of doping. Yet, if the results of these procedures are doubtful, then doubt must be interpreted in favor of the athlete concerned.